2000
DOI: 10.1002/srin.200005698
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of steel deoxidization processes during tapping and refining operations

Abstract: A thermodynamic model based on the interaction parameter approach for molten metal solutions and a quasi‐chemical model for molten slags and non‐metallic inclusions was employed to analyze steel deoxidization during tapping and refining operations in a ladle furnace. This model is able to predict the mineralogical nature of non‐metallic inclusions and their amount through thermodynamics and mass balances. It was found that the addition sequence of deoxidizers during a tapping procedure influences the nature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Assuming thermodynamic equilibrium, complete mixing conditions and efficient ferroalloys dissolution, the group of the authors demonstrated that the amounts and types of inclusion chemistries depend on the addition sequence during steel tapping, steel level in the ladle and oxygen concentration in the melt. 4,5) Therefore, those findings underline the importance of an efficient mixing process assisted by the momentum transfer effects of the jet plunging into the melt. Final oxygen levels, assuming thermodynamic equilibrium during steel tapping, depend then on efficient mixing and melting-dissolution processes of ferroalloys and aluminum.…”
Section: Introductionmentioning
confidence: 85%
“…Assuming thermodynamic equilibrium, complete mixing conditions and efficient ferroalloys dissolution, the group of the authors demonstrated that the amounts and types of inclusion chemistries depend on the addition sequence during steel tapping, steel level in the ladle and oxygen concentration in the melt. 4,5) Therefore, those findings underline the importance of an efficient mixing process assisted by the momentum transfer effects of the jet plunging into the melt. Final oxygen levels, assuming thermodynamic equilibrium during steel tapping, depend then on efficient mixing and melting-dissolution processes of ferroalloys and aluminum.…”
Section: Introductionmentioning
confidence: 85%
“…In the tapping process of steel, liquid steel with a mass of Dm BOFÀst (Eq. [1]) is tapped from the BOF to the ladle at each time step (Dt). The tapping flow rate (V st ) is calculated in Eq.…”
Section: Modelingmentioning
confidence: 99%
“…Modeling simulation is an effective method to study the reactions in the steel tapping and refining process. Galindo et al [1] proposed a thermodynamic model on steel deoxidation processes during tapping and refining. In the model, the thermodynamic equilibrium of inclusion and metal, inclusion and entrapped slag by steel and mass balance were considered, while the interfacial reaction of steel and slag was not accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Steel tapping is crucial for plant productivity and the steel quality depends on this operation. Its importance is demonstrated by a fundamental science such as thermodynamics demonstrating that the sequence and order of deoxidants and fluxes during steel tapping operations influence the residual content of oxygen and the type of inclusions [1]. The efficiency (measured as the dissolved amount by the total weight of the addition) of the alloys depends on the oxidation of the bath and the fluid dynamics of mixing.…”
Section: Introductionmentioning
confidence: 99%